Natural Small Molecules Targeting NF-κB Signaling in Glioblastoma - Uddin, Md. Sahab; Kabir, Md. Tanvir; Mamun, Abdullah Al; Sarwar, Md. Shahid; Nasrin, Fatema; Emran, Talha Bin; Alanazi, Ibtesam S.; Rauf, Abdur; Albadrani, Ghadeer M.; Sayed, Amany A.; Mousa, Shaker A.; Abdel-Daim, Mohamed M. (Frontiers in Pharmacology, 2021)
Nuclear factor-κB (NF-κB) is a transcription factor that regulates various genes that mediate various cellular activities, including propagation, differentiation, motility, and survival. Abnormal activation of NF-κB is a common incidence in several cancers. Glioblastoma multiforme (GBM) is the most aggressive brain cancer described by high cellular heterogeneity and almost unavoidable relapse following surgery and resistance to traditional therapy. In GBM, NF-κB is abnormally activated by various stimuli. Its function has been associated with different processes, including regulation of cancer cells with stem-like phenotypes, invasion of cancer cells, and radiotherapy resistance identification of mesenchymal cells. Even though multimodal therapeutic approaches such as surgery, radiation therapy, and chemotherapeutic drugs are used for treating GBM, however; the estimated mortality rate for GBM patients is around one year. Therefore, it is necessary to find out new therapeutic approaches for treating GBM. Many studies are focusing on therapeutics having less adverse effects owing to the failure of conventional chemotherapy and targeted agents. Several studies of compounds suggested the involvement of NF-κB signaling pathways in the growth and development of a tumor and GBM cell apoptosis. In this review, we highlight the involvement of NF-κB signaling in the molecular understanding of GBM and natural compounds targeting NF-κB signaling.